Three Coaching Priorities for Enhancing Teacher Practice in Disciplinary Literacy Instruction in the English Language Arts - Di Domenico, Paula; Elish-Piper, Laurie; Manderino, Michael; L'Allier, Susan K (Journal of adolescent & adult literacy, 2019)
Discipline-specific literacy instruction is key to supporting adolescents' overall literacy development. Job-embedded professional development that supports teachers' discipline-specific literacy instruction via instructional coaching is a promising approach to enacting disciplinary literacy instruction in English language arts (ELA) classrooms. Findings from a multiyear study of instructional coaching yielded three priorities that coaches can use as a guide when collaborating with ELA teachers: ensuring that collaboration is sustained over time, considering teachers' knowledge to create a coaching plan, and adopting a distributed expertise approach to create a collaboration in which both coach and teacher have ownership in the process. Examples from the multiyear study and suggestions for coaches' practice when working with ELA teachers are shared.